2020
DOI: 10.48550/arxiv.2010.07059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Symmetries of the Black Hole Interior and Singularity Regularization

Marc Geiller,
Etera R. Livine,
Francesco Sartini

Abstract: We reveal an iso(2, 1) Poincaré algebra of conserved charges associated with the dynamics of the interior of black holes. The action of these Noether charges integrates to a symmetry of the gravitational system under the Poincaré group ISO(2, 1), which allows to describe the evolution of the geometry inside the black hole in terms of geodesics and horocycles of AdS 2 . At the Lagrangian level, this symmetry corresponds to Möbius transformations of the proper time together with translations. Remarkably, this is… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 94 publications
(142 reference statements)
9
20
0
Order By: Relevance
“…[41] that the Schwarzschild-(A)dS mechanics possesses a set of dynamical symmetries under the Poincaré group SL(2, R) ⋉ R 3 , extending previous results in Ref. [42]. In particular, the Schwarzschild background was shown to be covariant under the Möbius symmetry transformation provided the metric functions transform with a suitable conformal weight 7 .…”
Section: Discussionsupporting
confidence: 82%
“…[41] that the Schwarzschild-(A)dS mechanics possesses a set of dynamical symmetries under the Poincaré group SL(2, R) ⋉ R 3 , extending previous results in Ref. [42]. In particular, the Schwarzschild background was shown to be covariant under the Möbius symmetry transformation provided the metric functions transform with a suitable conformal weight 7 .…”
Section: Discussionsupporting
confidence: 82%
“…In this paper special focus has been put on effective polymer models as symmetry reduced LQG models [1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Without specifying a concrete model, it was already possible to deduce the qualitative properties of the collapsing surface.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…A common way to study black holes in quantum gravity is to study eternal black holes [1,12,13,16,17,19,21,22,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]87], which is of course not the scenario that takes place in nature. Using the matching conditions (2.19) provides us with a strategy to extend the eternal black hole model to a dust collapse model according to the interpretation of Sec.…”
Section: Application To Effective Black Hole Metrics -Polymer Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary results along that line have been obtained recently. By considering the anisotropic Kantowski-Sachs cosmological model, which describes the Schwarzschild interior mechanics, it was shown that the SL(2, R) symmetry group found in the isotropic case is enhanced to the three dimensional Poincaré group SL(2, R) ⋉ R 3 [28]. The charge algebra associated to this symmetry group allows one to reconstruct the black hole interior dynamics.…”
Section: Introductionmentioning
confidence: 99%